Estimating the value-added tax gap in Tanzania: A study of small, medium, and micro enterprises - Amina Ebrahim; Sebastián Castillo; Vincent Leyaro; Ezekiel Swema; Oswald Haule; Massaga Fimbo; Ephraim Mdee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study measures the VAT compliance gap for small and medium-sized entities in Tanzania. Specifically, the study measures the under-reporting component of the VAT compliance gap. This study uses VAT declaration and audit data to conduct a bottom-up estimation to measure the extent of VAT misreporting in small, medium, and micro enterprises. The study's objective is to examine the extent of VAT under-reporting from 2014 to 2020 and identify the behaviour of firms that contribute to the VAT gap. The study finds a VAT gap of 62%, with the largest gaps in the agriculture, transportation, and manufacturing sectors. The accommodation, professional, wholesale and retail, and manufacturing sectors drive the overall VAT gap and are thus more important in identifying VAT revenue losses. The study provides evidence of firms' strategic reporting behaviour to avoid being audited, which increases the possibility of VAT evasion. Lastly, the study provides a cost-benefit ratio to make cost-effective recommendations to redistribute resources to increase auditing in sectors with more considerable evasion and lower audit probability.
Keywords: H25; H26; H32; 330; VAT compliance gap; bottom-up estimation; audit; under-reporting; Tanzania